제시양식 및 부호화조건과 단서양식이 아동의 회상에 미치는 영향 - 박명자(Myung Ja Park); 최경숙(Kyung Sook Choi) (Korean Journal of child studies, 1990)
The purpose of the present study was to investigate the age-related differences in recall and to assess effects of presentation modality, encoding condition and cue modality on recall in terms of encoding specificity principles and dual-coding theory. Eighty children in each of 3grades(first, third and fifth) were presented a 30-item set of pictures or words on cars for recall in a study-test procedure. The experiment was designed as a 3(age) x 2(presentation modality:picture or word) x 2(encoding condition:random or category) x 2(cue modality:picuture or word) factorial design. Statistical analyses were with four-way ANOVA and $Scheff\acute{e}$ test. It was concluded from these results that when the stimulus was presented by pictures, encoded by category and the cues were also presented by pictures, recall increased in all ages. These results were interpreted in terms of encoding specificity principles and dual-coding theory.